Australia : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
In 2000, Australia entered the tenth year of an impressive economic expansion characterized by strong productivity growth and low inflation. The Australian equity market performed better than most countries in the region in local currency terms, and spreads on long-term government bonds and on private sector debt remained steady. Executive Directors observed that the means-tested publicly provided age pension, the mandatory private superannuation scheme, and the tax incentives for additional voluntary saving provide a suitable framework for retirement income support over the long term.